Efektivitas Program Pelatihan Dan Pengembangan Terhadap Kinerja Karyawan Puskesmas Kotagede 2 Yogyakarta - Ika Septiani; Bangun Putra Prasetya (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
At this time, every company or organization must always innovate and update its human resources by providing training and development programs for its employees. By doing this, the company can compete with other companies in all fields. The purpose of this study is to evaluate the effect of training and development on employee performance at the Kotagede 2 Yogyakarta Health Center. The results and language of the study indicate that training (X1) and development (X2) have a positive impact on employee performance (Y) at Puskesmas Kotagede 2 Yogyakarta, and development (X2) has a positive impact on performance (Y).